2015
DOI: 10.1177/1479972315602618
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French version of the Leicester Cough Questionnaire in chronic obstructive pulmonary disease

Abstract: Cough is one of the three major symptoms reported by chronic obstructive pulmonary disease (COPD) patients. The Leicester Cough Questionnaire (LCQ) is a questionnaire exploring the impact of cough, but it does not exist in French. The aim of this study was to develop a French version of LCQ and to assess its psychometrics properties. A forward-backward translation process was used to develop the French version of the LCQ. COPD patients completed LCQ and Cough and Sputum Assessment Questionnaire (CASA-Q) to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
(36 reference statements)
2
3
2
Order By: Relevance
“…This may explain the observed ceilings effects and why impact of cough and sputum in the HRQoL of our participants was comparable to other studies enrolling patients with COPD, 31,56 but different (our sample scored better) from studies considering patients with chronic cough only. 28,57,58 Although previous research has showed a relationship between CAT and cough and sputum, 59,60 in our study an association was verified only with cough. However, association was explored with mean changes, while previous studies have focused on absolute scores.…”
Section: Discussioncontrasting
confidence: 81%
“…This may explain the observed ceilings effects and why impact of cough and sputum in the HRQoL of our participants was comparable to other studies enrolling patients with COPD, 31,56 but different (our sample scored better) from studies considering patients with chronic cough only. 28,57,58 Although previous research has showed a relationship between CAT and cough and sputum, 59,60 in our study an association was verified only with cough. However, association was explored with mean changes, while previous studies have focused on absolute scores.…”
Section: Discussioncontrasting
confidence: 81%
“…12,16 The LCQ has been also validated in other languages in chronic cough [33][34][35] and in COPD. 36,37 The results in repeatability and concurrent validity measured with different questionnaires are similar to our results. [33][34][35][36][37] Responsiveness has been studied at 2 or 6 months after improvement or treatment but not at the beginning of an exacerbation.…”
Section: Discussionsupporting
confidence: 88%
“…36,37 The results in repeatability and concurrent validity measured with different questionnaires are similar to our results. [33][34][35][36][37] Responsiveness has been studied at 2 or 6 months after improvement or treatment but not at the beginning of an exacerbation. No data about feasibility, discriminant validity were reported.…”
Section: Discussionsupporting
confidence: 88%
“…In the Turkish validity study of the LCQ in patients with chronic cough, the relationship between LCQ subscales and SF-36 subscales was found to be significant, in parallel with our study (5). Kwon (25). The study of Birring et al also showed that the LCQ is suitable for use in many areas.…”
Section: Discussionmentioning
confidence: 99%
“…Sönnerfors et al also showed that the questionnaire correlated with the Swedish version of the LCQ with the St George's Respiratory Questionnaire and the COPD Assessment Test, and indicated that the questionnaire could be used (24). Reychler et al also tested the French version of the questionnaire with the Cough and Sputum Assessment Questionnaire and found a strong correlation (25). The study of Birring et al also showed that the LCQ is suitable for use in many areas.…”
Section: Discussionmentioning
confidence: 99%